Transchromosomic bovine-derived anti-SARS-CoV-2 polyclonal human antibodies protects hACE2 transgenic hamsters against multiple variants - Gilliland, Theron; Dunn, Matthew; Liu, Yanan; Alcorn, Maria D.H.; Terada, Yutaka; Vasilatos, Shauna; Lundy, Jeneveve; Li, Rong; Nambulli, Sham; Larson, Deanna; Duprex, Paul; Wu, Hua; et al. (iScience, 2023)
Pandemic SARS-CoV-2 has undergone rapid evolution resulting in the emergence of many variants with mutations in the spike protein, some of which appear to evade antibody neutralization, transmit more efficiently, and/or exhibit altered virulence. This raises significant concerns regarding the efficacy of anti-S monoclonal antibody-based therapeutics which have failed against variant SARS-CoV-2 viruses. To address this concern, SAB-185, a human anti-SARS-CoV-2 polyclonal antibody was generated in the DiversitAb platform. SAB-185 exhibited equivalent, robust in vitro neutralization for Munich, Alpha, Beta, Gamma, and Δ144-146 variants and, although diminished, retained PRNT50 and PRNT80 neutralization endpoints for Delta and Omicron variants. Human ACE2 transgenic Syrian hamsters, which exhibit lethal SARS-CoV-2 disease, were protected from mortality after challenge with the Munich, Alpha, Beta, Delta, and Δ144-146 variants and clinical signs after non-lethal Omicron BA.1 infection. This suggests that SAB-185 may be an effective immunotherapy even in the presence of ongoing viral mutation. [Display omitted] •A transchromosomic bovine polyclonal antibody neutralizes variants of SARS-CoV-2•We use a novel human ACE2 (hACE2) transgenic hamster model of SARS-CoV-2 infection•The polyclonal antibody protects hACE2 hamsters from all variants tested•Hyperimmunization of the bovines may promote protection against SARS-CoV-2 variants Immunology; Immune response; Virology